Module 1: Philosophy of Islamic Education - Wan Yusoff, Wan Mazwati (2021)
This module is developed based on extensive reviews of the literature on the Philosophy of Islamic Education by prominent scholars from the medieval period to the present time. Such scholars are Imam al-Ghazali, Ibn Khaldun, al-Atlas, al-Faruqi, Muhammad Kamal